Density‐dependent effects of mortality on the optimal body size to shift habitat: Why smaller is better despite increased mortality risk. (1st May 2020) - Chaparro‐Pedraza, P. Catalina; de Roos, André M.
Abstract: Many animal species across different taxa change their habitat during their development. An ontogenetic habitat shift enables the development of early vulnerable‐to‐predation stages in a safe "nursery" habitat with reduced predation mortality, whereas less vulnerable stages can exploit a more risky, rich feeding habitat. Therefore, the timing of the habitat shift is crucial for individual fitness. We investigate the effect that size selectivity in mortality in the rich feeding habitat has on the optimal body size at which to shift between habitats using a population model that incorporates density dependence. We show that when mortality risk is more size dependent, it is optimal to switch to the risky habitat at a smaller rather than larger body size, despite that individuals can avoid mortality by staying longer in the nursery habitat and growing to safety in size. When size selectivity in mortality is high, large reproducing individuals are abundant and produce numerous offspring that strongly compete in the nursery habitat. A smaller body size at habitat shift is therefore favored because strong competition reduces growth potential. Our results reveal the interdependence among population structure, density dependence, and life history traits, and highlight the need for integrating ecological feedbacks in the study of life history evolution.